2009
DOI: 10.1002/ccd.22275
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous management of a Fontan fenestration: In search for the ideal restriction—occlusion device

Abstract: Objective: Most devices devices available for percutaneous closure of Fontan fenestrations tend to be bulky. The aim of this study was to evaluate a low profile custom made device and assess its efficacy and safety. Patients and Methods: A 15 mm PFO star was used as the basis. The following modifications were made: removal of the left disc to reduce thrombogenicity in the left atrium, increase the length of the LA legs from 2 by 15 mm to 3 by 20 mm to prevent dislodgement and later adding a pivot between the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Continuous right-to-left shunting results in systemic oxygen desaturation and can prompt the occurrence of paradoxical embolism. Several percutaneous catheterization methods with different devices have been described for complete fenestration's closure [3,4,11,[15][16][17]. Mid-term and long-term observations after complete closure of the fenestration have consistently confirmed that mortality and morbidity is not increased and that patients constantly profit with improved oxygenation, reduced need for anticongestive medication, and improved somatic growth [3,18].…”
Section: Fontan Fenestrations In Failing Fontan Hemodynamicsmentioning
confidence: 93%
See 1 more Smart Citation
“…Continuous right-to-left shunting results in systemic oxygen desaturation and can prompt the occurrence of paradoxical embolism. Several percutaneous catheterization methods with different devices have been described for complete fenestration's closure [3,4,11,[15][16][17]. Mid-term and long-term observations after complete closure of the fenestration have consistently confirmed that mortality and morbidity is not increased and that patients constantly profit with improved oxygenation, reduced need for anticongestive medication, and improved somatic growth [3,18].…”
Section: Fontan Fenestrations In Failing Fontan Hemodynamicsmentioning
confidence: 93%
“…The concept of partial closure of interatrial comunications is a newly derived therapy, with only case reports or small series cited in the literature, while indications and procedure still have to be defined [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, numerous techniques have been developed to close these surgically created communications using devices primarily created for other indications, including ASD occluders, patent foramen ovale occluders, VSD occluders, embolization coils, vascular plugs, and covered stents. [65][66][67][68][69][70][71] Typically, after a complete right and left hemodynamic catheterization and angiography are performed, the fenestration is crossed from a transvenous approach and temporarily occluded for a period of time (typically between 10 and 20 minutes). If hemodynamics are deemed acceptable with the fenestration temporarily occluded (improved systemic oxygen saturation associated with only a modest rise in Fontan pressure or fall in cardiac output), a device is selected to use for permanent fenestration closure.…”
Section: Fontan Fenestrationmentioning
confidence: 99%
“…Ehhez olyan eszkö-zöket használtak, amelyeket eredetileg egyéb célokra fejlesztettek ki, mint például pitvari septumdefektus-occluderek, foramenovale-occluderek, kamrai septumdefektus-occluderek, embolisatiós coilok, vascularis elzáróeszközök és fedett stentek. [65][66][67][68][69][70][71] Általában a teljes jobb és bal oldali hemodinamikai katéterezés és angiográfia elvégzése után a fenesztráción transvenosus megközelítéssel jutunk át, és azt egy időre (általában 10-20 percre) átmenetileg elzárjuk. Ha a beteg hemodinamikai értékeit a fenesztráció átmeneti elzárása után is elfogadhatónak tartjuk (javuló szisztémás oxigénszaturáció, amit csak a Fontan-nyomás kismértékű emelkedése és a perctérfogat kismérté-kű csökkenése kísér), kiválasztjuk a megfelelő eszközt a fenesztráció tartós zárására.…”
Section: A Fontan-fenesztráció éS a Terelőfolt-szivárgás Zárásaunclassified
“…(10,124) Later percutaneous closure of the fenestration is often performed if cyanosis is profound and may be complete occlusion (125)(126)(127) or partial. (128,129) Similarly, baffle leaks in the suture line of the fontan circuit, may lead to cyanosis which may be closed percutaneously. (130) Venous collaterals are also common and may be addressed in the catheter lab.…”
Section: Cyanosismentioning
confidence: 99%